Dynamic magnetic properties of mn doped YBa2Cu3O7_δ superconducting ceramics / S. A. Halim ... [et al.] - Halim, S. A.; Tien, C.Y; Hamadneh, Imad; Tarmizi, A.K.M; H., Azhan; Mustafa, M.D; Sidek, H.A.A; W. Yusoff, W. Daud; Suradi, J. (2002)
AC complex susceptibility, X = X' + i X", measurements were done on the YBa2Cu3O7_δ superconducting samples doped with Mn at Y, Ba and Cu sites Y123 with nominal starting composition (x = 0.02 and 0.1). The data of X' shows that the coupling of the grains in samples that doped at Cu site are weaker than that samples doped at Y and Ba sites as shown by using the Ambegaokar-Baratoff equation 10 = 1.57 x 108Tc2-/( Tc-Tej), the calculated values of Josephson current, 10 where 1o(in y > l0(in Ba) > 10(in Cu) due to the weakening of the grain's coupling. This observation is supported by the intrinsic coupling loss, Tp obtained from X" that shows a bigger shift of the intergranular coupling peak, Tp, towards lower temperature in Mn doping at Cu site as compared to the doping in Ba and Y sites. Hence the effect of doping is obvious at higher concentration for all samples. Analysis based on the sensitivity of the data of dx'/dT versus temperature furnished further information on the two step transition related to the coupling of the grains in all systems.